Fashion writing a textual analysis of selected fashion articles - Pugat, Rogelio S. Jr.; Orendain, Iskra Gabrielle R. (2002.)
The most essential prerequisites of fashion writing is the need for fashion information brought about by people's interest in fashion. Vogue and Harper's Bazaar are two of the world's earliest fashion publications that have been answering to this need the world over. In the Philippines, two relatively younger magazines come tho mind when and where fashion is concerned: Metro and Mega. All four magazines provide the Filipino reader with the freshest fashion information every month. But what is it that sets local fashion magazines apart from foreign fashion publication? What is it that makes them similar? Although similarities and differences may be initially obvious in local and foreign magazines' general content, the more significant similarities and differences lie within their fashion texts. And with this assumption, it has been the objective of this study to determine, through textual analysis, the similarities and differences between fashion writing for Vogue, Harper's Bazaar, Metro, and Mega. Three articles from each magazine, dated between January to December 2001, were collected. As tools for this study, the standards of textuality - cohesion, coherence, situationality, intertextuality, and informativity - were used to analyze the chosen local and foreign fashion text. These standards were used together with the qualities of clarity, correctness, vividness and appropriateness, and the tools for rhetorical analysis (narration, description, procedure/process, argumentation). These tools, altogether, helped in determining the similarities and differences between fashion writing for Vogue, Harper's Bazaar, Metro, and Mega. They also aided in determining whether there are consistencies/inconsistencies in fashion writing within certain issues of each magazine. The major differences between fashion writing for Vogue, Harper's bazaar, Metro, and Mega lay mainly in the overall presentation of the fashion texts, that is, the length, writing style, language use, overall mood of the text and the amount of information conveyed by the text. All these elements of presentation are interrelated.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Fashion writing